Dietitian-led cluster randomised controlled trial on the effectiveness of mHealth education on health outcomes among pregnant women: a protocol paper - Ying, Ting Er; Yoke, Mun Chan; Mohd Shariff, Zalilah; Abdul Hamid, Habibah; Mat Daud, Zulfitri 'Azuan; Heng, Yaw Yong (BMJ Publishing Group, 2023)
Introduction Nutrition education is the cornerstone to maintain optimal pregnancy outcomes including gestational weight gain (GWG). Nevertheless, default for appointments is common and often lead to suboptimal achievement of GWG, accompanied with unfavourable maternal and child health outcomes. While mobile health (mHealth) usage is increasing and helps minimising barriers to clinic appointments among pregnant mothers, its effectiveness on health outcomes has been inconclusive. Therefore, this study aimed to address the gap between current knowledge and clinical care, by exploring the effectiveness of mHealth on GWG as the primary outcome, hoping to serve as a fundamental work to achieve optimal health outcomes with the improvement of secondary outcomes such as physical activity, psychosocial well-being, dietary intake, quality of life and sleep quality among pregnant mothers.